(untitled) (Bangladesh Journal of Medical Microbiology, 2013)
A multi-staged cross sectional study was conducted among children aged 2 -17 years to assess the level of soil transmitted helminthes (ST H) infections and its relation to socio-demographic characteristics among them. Two thousand children were randomly selected from two rural and four different communities of urban areas of Dhaka district since November 2009 to June 2010. Four different communities classified as higher, medium, poorer and slum/ low socio-economic groups from urban areas were selected on the basis of their place of residence with different socio-economic status. Urban study subjects were again sub grouped into upper (higher and medium socio-economic) and lower (poorer and slum/low socio-economic) classes. Stool specimens of the respondents were collected and tested at the Parasitology department of I E DCR , using the Kato-katz faecal technique for identification of helminthes eggs following their morphology (A. lumbricoides, Ttrichiura, and A. duodenale), and larval stage (S. stercoralis). About 32.15% study population harbored at least one of the four helminthes species. Baseline prevalence of infections and mean parasite loads for Ascaris lumbricoides were 40.61% and 600.80 e/g, for Trichuris trichiura 30.42% and 206.11e/g, and for A. duodenale 6.80% and 78.75 e/g. Three children (0.49%) were positive for Strongyloides stercoralis. Single infection of 78.32 % and double infection of 21.68 % were recorded. Single infection of A. lumbricoides (40.61%) and T trichiura (30.42%) and double infection of A. lumbricoides - T trichiura (18.61%) were more prevalent. T he prevalence of ST H infection was 25.47 % and 38.68 % for rural and urban areas respectively (P<.001). Among urban study subjects, the distribution of ST H infection was 0.0 % in the higher (living in higher socioeconomic areas) (only 3 samples could be collected), 26.75 % in medium (living in medium socio-economic areas), 45.95 % in poorer and 50.54 % in slum/low socio-economic groups. Significantly higher number of ST H infection was observed among lower than that in upper socio-economic classes (P <.001). These results suggest that ST H infections remain a serious health problem among children in Bangladesh and need appropriate prevention and control measures. DOI: http://dx.doi.org/10.3329/bjmm.v5i2.16933 Bangladesh J Med Microbiol 2011; 05 (02): 16-22